Proteína hidrolisada de aves e suínos em dietas para alevinos (tilápia do Nilo): desempenho produtivo e sobrevivência - Santos, Adriano José Führ dos (2020)
The present study aimed to evaluate the effects of increasing levels of inclusion in the diet of protein hydrolyzate composed of co-products of poultry and swine (giblets and liver) on the growth and stress resistance of Nile tilapia fry. For this purpose, 360 tilapia fingerlings with an average weight of 1.10 ± 0.07 g were used, randomly distributed in 24 polyethylene boxes (15 fish per box) with a capacity of 250 L, constituting six treatments with four replicates. The isoproteic and isoenergetic rations supplied until satiety five times a day, for 45 days and were formulated to contain 0.0; 0.3; 0.6; 0.9; 1.2 and 1.5% inclusion of hydrolyzed chicken protein (PHF) and hydrolyzed porcine liver protein (PHFS). At the end of the experimental period, the number of fish in each aquarium was counted and the weight and length of all individuals were measured to assess the influence of the hydrolyzate on zootechnical performance, where the parameters evaluated were the final weight, standard length final, specific growth rate, protein efficiency rate, condition factor and survival. The best hydrolyzate inclusion value obtained was 0.311% for final weight, 0.187% for final standard length, 0.205% for specific growth rate and 0.321% for protein efficiency rate, so as not to have influenced the condition factor and survival when compared to the control treatment, absent from the test ingredient.